Ответы и объяснения

2013-04-28T12:21:04+00:00

1)  x/6+y/3=2               x+16-2x=12            -x=-4
      x+y=8           <=>   y=8-x                <=>  y=4  


2)   4x^2-4x+1-4x^2+12x-9=8y               x-1=y                   y=x-1              y=-1
       y^2-4y+4-y^2-8y-16=6x           <=>  -2y-2=x   <=>    3x=0   <=>      x=0

Лучший Ответ!
2013-04-28T12:34:42+00:00

1) x+y=8

x=8-y

(8-y) / 6  = y/3 =2

(8-y+2y) /6 =2

8=y=12

y=4

x=8-4=4

 

2) 4x-4x+1-(4x+12x+9)=8y

y^2 - 4y+4-(y^2 +8y+16)=6x

 

4x-4x+1-4x-12x-9=8y

y^2 -4y+4-y^2 -8y-16=6x

 

-16x-8y=8        ]*(-3)

-12y-6x=12      ]*2

 

48x+24y=-24

-12x-24y=24

-------------------

36x=0

x=0

48*0 +24y=-24

24y=-24

y=-1